Application of ductility exhaustion based damage model to predict creep rupture time of grade 92 steel - Nasrul Azuan, Alang; N., Ab Razak (IOP Publishing, 2019)
To accurately predict the creep rupture time of notched bar becomes a challenge to academia and structural engineer due to complex stress-strain distribution around the notch throat. This paper presents a Finite Element (FE) simulation employing ductility exhaustion based damage model to predict creep rupture time of multiaxial notched bar Grade 92 steel. Three different notch acuity, ƞ = 2.5, 5.0 and 12.0 were simulated and the FE predicted rupture time was compared to the available experimental rupture data. The reduction of creep ductility due to geometrical constraint is considered during the simulation by employing the void growth model. Further reduction in ductility at long term period arise from internal microstructural changes or damage is also accounted. Furthermore, empirical-type exponential prediction model coupled with skeletal stresses is applied to provide upper/lower bounds for short and long term rupture data. It is found that the FE prediction agreed well with the experimental data. At short-term, notched bar ruptured is controlled by the von-Mises stress while at long-term the rupture is controlled by the maximum principal stress.